2021
DOI: 10.1136/bcr-2021-243506
|View full text |Cite
|
Sign up to set email alerts
|

Malignant idiopathic intracranial hypertension revealed a hidden primary spinal leptomeningeal medulloblastoma

Abstract: Frequently the cause of raised intracranial pressure remains unresolved and rarely is related to spinal tumours, moreover less to spinal medulloblastoma without primary brain focus. An 18-year-old woman had a 3-month history of headache and impaired vision. Neurological examination revealed bilateral sixth cranial nerve palsies with bilateral papilloedema of grade III. No focal brain or spine lesion was found on imaging. Consecutive lumbar punctures showed high opening pressure and subsequent increasing protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…20 Some authors have demonstrated the presence of neoplastic cells in the CSF. 7,10,18 Similar to others, 4,6,9 in our case, no neoplastic cells were identified in the CSF sample.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…20 Some authors have demonstrated the presence of neoplastic cells in the CSF. 7,10,18 Similar to others, 4,6,9 in our case, no neoplastic cells were identified in the CSF sample.…”
Section: Discussionsupporting
confidence: 89%
“…Generally, PL-MB manifests with headache 4 6 8 10 12 18 and visual abnormalities 4 6 8 10 18 lasting a few months, and may also result in rapid neurologic deterioration. 8 9 11 12 In particular, Hankey et al 4 described the case of a 39-year-old woman presenting with a month-long history of headaches, slurred speech, ataxia, memory impairment, and olfactory and auditory hallucinations.…”
Section: Discussionmentioning
confidence: 99%